What she said, what he said: local elected officials' views of effective leadership behaviors. Issue 2 (15th February 2021) - Dula, Lauren; Holmes, Maja Husar; Jacobson, Willow S.; Lambright, Kristina T.
Abstract : Purpose: This study advances understanding of the behaviors local elected officials believe effective leaders display, whether these behaviors tend to be associated with a particular gender and if beliefs vary by gender. Design/methodology/approach: Using data from focus groups with local elected officials in a US state, participants were asked to identify behaviors of effective elected officials. Focus group demographic data allowed for responses to be matched by the participants' gender. Findings: Men and women local elected officials differ little in their beliefs about what behaviors make leaders effective. The most commonly mentioned behaviors are more likely to be associated with women or are gender-ambiguous. Originality/value: This study contributes to the leadership literature by examining local elected officials' beliefs about effective leadership behaviors and if these beliefs differ by a respondent's gender.